Western dietary pattern is associated with higher risk of lower lean muscle mass in Korean postmenopausal women: data from the Korea National Health and Nutrition Examination Survey 2008-2011 - Vijayakumar, Aswathy; Kim, Yangha; Kim, Hyesook; Kwon, Oran (Nutrition research and practice, 2021)
In a healthy person, from 35 years of age, there is an annual loss of muscle mass at the rate of 1-2% and is associated with a decline in the quality of life. This study aimed to identify the particular dietary patterns associated with the risk of lower lean muscle mass in Korean postmenopausal women.BACKGROUND/OBJECTIVESIn a healthy person, from 35 years of age, there is an annual loss of muscle mass at the rate of 1-2% and is associated with a decline in the quality of life. This study aimed to identify the particular dietary patterns associated with the risk of lower lean muscle mass in Korean postmenopausal women.The Korea National Health and Nutrition Examination Survey (KNHANES) is a population-based, continuous cross-sectional annual survey. The participants of the KNHANES IV (2008-2009) and V (2010-2011) were considered for this study. The study sample consisted of 1548 postmenopausal women, aged 45-86 years. Lower lean muscle mass was defined as having appendicular skeletal muscle mass corrected for body weight less than 1 standard deviation of the young reference group aged 20 to 39 years in KNHANES IV and V. To identify the dietary pattern using factor analysis, 24-h recall data was used.SUBJECTS/METHODSThe Korea National Health and Nutrition Examination Survey (KNHANES) is a population-based, continuous cross-sectional annual survey. The participants of the KNHANES IV (2008-2009) and V (2010-2011) were considered for this study. The study sample consisted of 1548 postmenopausal women, aged 45-86 years. Lower lean muscle mass was defined as having appendicular skeletal muscle mass corrected for body weight less than 1 standard deviation of the young reference group aged 20 to 39 years in KNHANES IV and V. To identify the dietary pattern using factor analysis, 24-h recall data was used.The prevalence of lower lean muscle mass was 31.3% in this study population. Four dietary patterns were identified by factor analysis; 'Diverse', 'Western', 'Traditional', and 'Snacks and beverages'. The 'Western' pattern, highest factor loadings for flour and bread, potatoes, red meat, processed meat, eggs, and cheese, was significantly associated with a high (60%) risk of lower lean muscle mass (odds ratio [95% confidence interval] = 1.60 [1.07-2.39], P for trend = 0.01) after adjustments for potential covariates. The other 3 dietary patterns were not associated with lower lean muscle mass.RESULTSThe prevalence of lower lean muscle mass was 31.3% in this study population. Four dietary patterns were identified by factor analysis; 'Diverse', 'Western', 'Traditional', and 'Snacks and beverages'. The 'Western' pattern, highest factor loadings for flour and bread, potatoes, red meat, processed meat, eggs, and cheese, was significantly associated with a high (60%) risk of lower lean muscle mass (odds ratio [95% confidence interval] = 1.60 [1.07-2.39], P for trend = 0.01) after adjustments for potential covariates. The other 3 dietary patterns were not associated with lower lean muscle mass.The study findings suggest that the 'Western' dietary pattern that includes flour and bread, potatoes, red meat, processed meat, eggs, and cheese, may be associated with a higher risk of lower lean muscle mass in Korean postmenopausal women.CONCLUSIONSThe study findings suggest that the 'Western' dietary pattern that includes flour and bread, potatoes, red meat, processed meat, eggs, and cheese, may be associated with a higher risk of lower lean muscle mass in Korean postmenopausal women.